(untitled) (Research, Society and Development, 2021)
Objectives: To describe the nurses’ perception of the care provided to polytrauma patients in an Emergency Room (ER). Methodology: Qualitative, descriptive and exploratory study. The data were collected through semi-structured interviews and analyzed according to thematic analysis. Results: Seven nurses from an Emergency Room located in the south of Rio Grande do Sul participated in this study. The nurses perceive leadership as a differential in their category, with initiative during assistance and the ability to coordinate management and assistance actions. The absence of protocols was mentioned, however, they highlight that they carry out training and improvement courses to fill this lack. All nurses refer to poor infrastructure as a negative factor in care. In relation to easinesses in care, the performance of team activities stood out. Final considerations: The importance of investing in the improvement of these professionals is highlighted. The precarious infrastructure, with reduced spaces, became evident as a difficulty to perform the health care.